2014
DOI: 10.4049/jimmunol.1401984
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Innate Immune Receptor SIRPα Controls CD47 Binding and Autoimmunity in the Nonobese Diabetic Mouse

Abstract: The signal regulatory protein (SIRP) locus encodes a family of paired receptors that mediate both activating and inhibitory signals and is associated with type 1 diabetes (T1D) risk. The NOD mouse model recapitulates multiple features of human T1D and enables mechanistic analysis of the impact of genetic variations on disease. In this study, we identify Sirpa encoding an inhibitory receptor on myeloid cells as a gene in the insulin-dependent diabetes locus 13.2 (Idd13.2) that drives islet inflammation and T1D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…SIRPα engagement by its ubiquitously expressed monomorphic ligand CD47 delivers an inhibitory signal that represses phagocytosis by macrophages and inhibits multiple aspects of DC activation (1820). In some contexts, CD47-SIRPα signaling is bidirectional as SIRPα binding to CD47 triggers stimulatory signals in T cells and neurons (12, 21, 22). We therefore took a genetic approach to test whether donor SIRPα polymorphism controls the MHC-independent alloreactions we had observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SIRPα engagement by its ubiquitously expressed monomorphic ligand CD47 delivers an inhibitory signal that represses phagocytosis by macrophages and inhibits multiple aspects of DC activation (1820). In some contexts, CD47-SIRPα signaling is bidirectional as SIRPα binding to CD47 triggers stimulatory signals in T cells and neurons (12, 21, 22). We therefore took a genetic approach to test whether donor SIRPα polymorphism controls the MHC-independent alloreactions we had observed.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these functions, CD47 −/− mice were refractory to the induction of autoimmune diseases; for example, experimental allergic encephalomyelitis (38), experimental colitis (39), and murine lupus (40). In addition, Wong et al showed that enhanced binding of SIRPα to CD47 in the NOD mouse is a key determinant of the pathogenesis of autoimmune diabetes, likely due to the costimulatory actions of CD47 on T cells (12). Together, these data support our proposal that engagement of CD47 on recipient monocytes by SIRPα on graft cells provides an activation signal that causes monocyte proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this model is currently on the BALB/c background, it is likely that this will be developed on a NOD.scid background for T1D studies. SIRPalpha has already been shown to be important for diabetes susceptibility, both in terms of polymorphic variation and the level of protein expression [202]. Therefore developing these MISTRG mice on a NOD background will provide further discoveries into the pathogenesis of autoimmune diabetes.…”
Section: Humanized Nod Micementioning
confidence: 99%
“…Interestingly, some of the genes in this N et P oco are previously reported to be associated with T2D [52], while some may have links to T2D although no direct associations are previously reported. More precisely, Wong et al [53] show that SIRPA is a T1D risk gene in the non-obese diabetic mouse. The inclusion of this gene in a N et P oco that is used in risk assessment for T2D suggests that this gene can be a potential novel candidate for association with T2D as well.…”
Section: Resultsmentioning
confidence: 99%